The Implementation Effect and Innovation Analysis of Shenzhen Urban Employee Medical Insurance Policy - Rong, Guoming (International Journal of Social Sciences and Public Administration, 2024)
This paper will review Shenzhen's urban employee medical insurance policy with an outline of its evolution, creative practices, and comprehensive system design that distinguishes it from the national standards. The paper allows a tracing of the evolution of medical insurance in China and, more specifically, Shenzhen's pioneering role in this sector since the early 1980s. The study focuses on the dynamics of revenues and expenditure of the pooling fund and individual accounts in respect of financial sustainability and efficiency, it covers inpatient, outpatient, medication, and special medical services, and it deals with the age structure of the insured population. It contrasts the policy practices of Shenzhen with the national standard, highlighting the city's innovativeness in adopting the Family Medical Savings Account system and other advanced digital technologies. The review of how policies have been implemented focuses on the positive impact of the changes on health outcomes and economic burdens but also on the challenges and future directions to develop the system. The approach Shenzhen has adopted offers valuable lessons and becomes a model for developing inclusive, equitable, and sustainable healthcare solutions for other regions.